Assembly and comparative analysis of the complete mitochondrial genome of Abies beshanzuensis: insights into conservation genomics of a critically endangered fir - Xingjian Liu; Shiyu Hu; Jiahao Shen; Mimi Li (BMC Plant Biology)
Abstract Background Abies beshanzuensis, an endemic fir native to the subtropical high mountains of eastern China, is classified as a first-class nationally protected wild plant and is listed as Critically Endangered (CR) by the International Union for Conservation of Nature (IUCN). Taxonomic controversies have long persisted among A. beshanzuensis, A. ziyuanensis, and A. dayuanensis, yet studies focusing on their mitochondrial DNA remain limited. Results In this study, the complete mitochondrial genome of A. beshanzuensis was assembled using a combination of Oxford Nanopore long-read sequencing and Illumina short-read sequencing technologies. The mitochondrial genome is 1.06 Mb in size with a GC content of 45.97%, and consists of nine linear chromosomes and one circular chromosome. Comprehensive analyses, including genome annotation, structural comparisons, RNA editing site prediction, and phylogenetic reconstruction, were subsequently conducted. Conclusion The results provide important insights into the mitochondrial genome architecture of A. beshanzuensis, offering a valuable resource for clarifying its controversial taxonomic status and advancing the understanding of evolutionary relationships within the genus Abies.